Pemanfaatan E-Application Dalam Peningkatan Proses Audit Mutu Internal (Studi Kasus : Universitas Bina Nusantara) - Cuk Tho; Wihendro Wihendro; Yohannes Kurniawan (ComTech: Computer, Mathematics and Engineering Applications, 2010)
This paper shows the use of e-application to assist the implementation of internal quality audit, which is one of the conditions to be met within the requirements of ISO 9000 Quality Assurance System. E-application that is used other than as a data repository is also used as a workflow. Where is the workflow that is made will ensure that the repairs is carried out in accordance with what has been planned. As one of the ISO documentation requirements in Clause 4.2.4 that a document should be done traceable, then the use of e-application is very helpful in conducting the search trail. In addition, the e-application allows auditors and auditees in filling the audit results, since it can be accessed from anywhere as well as due to web-based, it can be done from any computer without the need of an installation. E-application that was developed to function as a workflow and data repository that can be used as part of monitoring and data history which will help to improve the performance of the unit hence also improves performance of Bina Nusantara University.